A rapid and sensitive assay to quantify amino sugars, neutral sugars and uronic acid necromass biomarkers using pre-column derivatization, ultra-high-performance liquid chromatography and high-resolution mass spectrometry. (February 2023) - Salas, Erika; Gorfer, Markus; Bandian, Dragana; Wang, Baorong; Kaiser, Christina; Wanek, Wolfgang
Abstract: Microbial necromass comprises a large fraction of soil organic matter (SOM) due to the accumulation and stabilization of microbial residues from dead archaea, bacteria and fungi. Amino sugars, neutral sugars and uronic acids have been used as microbial necromass biomarkers to trace the origin and composition of microbial residues in the SOM pool. Due to the structural complexity of sugars, derivatization reactions and high-throughput analytical methods are required to separate and quantify these sugar-related compounds. Our aim was to develop a rapid and sensitive assay to measure amino sugar, neutral sugar and uronic acid compounds using pre-column 1-phenyl-3-methyl-5-pyrazolone (PMP) derivatization. PMP-derivatives were separated and quantified via reversed phase (RP) ultra-high-performance liquid chromatography (UPLC) coupled to high-resolution Orbitrap mass spectrometry (MS). The method was validated and applied on hydrolyzed peptidoglycans and the biomass of archaeal, bacterial, fungal and plant species, as well as with soils. This developed PMP method allowed the separation and quantification of 18 sugar-related compounds, including four amino sugars, three N-acetyl amino sugars, eight neutral sugars, and three uronic acids within 20 min. This PMP method showed a precision for isotope enrichment detection of 0.03–0.05 atom % 13 C for D-glucose and D-glucosamine. This is the first time talosaminuronic acid (deriving from archaeal pseudopeptidoglycan) was identified and quantified using PMP derivatization. The application of this novel PMP method on pure hydrolyzed biomass and soils, showed the successful chromatographic and mass spectrometric separation and quantification of amino sugar, neutral sugar and uronic acid compounds. A multivariate analysis using these sugar-related PMP derivatives showed a clustering of the species according to their respective taxonomic group (archaea, gram-positive bacteria, gram-negative bacteria, fungi and plants). The modified PMP method can be applied to identify and quantify soil microbial necromass biomarkers, as well as their contribution to SOM. The sensitive isotope tracer detection allows tracing isotopically labeled materials into necromass biomarkers in SOM pools. Highlights: 1-phenyl-3-methyl-5-pyrazolone (PMP) derivatization for necromass biomarkers via LC-Orbitrap MS. Common bacterial and fungal necromass biomarkers extended to plants and archaea. Talosaminuronic acid indicative for archaea, hexoses for plants. Sensitive to trace isotopically labeled substrates into necromass. Facile application to complex environmental samples (soils).